Flexible Electronics for Monitoring in vivo Electrophysiology and Metabolite Signals - Choi, Hye Kyu; Lee, Jin-Ho; Lee, Taek; Lee, Sang-Nam; Choi, Jeong-Woo (Frontiers in Chemistry, 2020)
Numerous efforts have been made to develop efficient biosensors for detecting analytes in the human body. However, biosensors are often developed on rigid materials, which limits their application on skin, organs, and other tissues in the human body where good flexibility is required. Developing flexible materials for biosensors that can be used on soft and irregularly-shaped surfaces would significantly expand the clinical application of biosensors. In this review, we will provide a selective overview of recently developed flexible electronic devices and their applications for monitoring in vivo metabolite and electrophysiology signals. The article provides guidelines for the development of an in vivo signal monitoring system and emphasizes research from various disciplines for further development of flexible electronics that can be used in more biomedical applications in the future.